Kesiapan Dan Kemampuan Mahasiswa Prodi Komunikasi Dan Penyiaran Islam Dalam Penerapan Dakwah Bil Lisan - Syatriadin Syatriadin (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2020)
The research carried out aims to determine the readiness and ability of the students of the Islamic Communication and Broadcasting Study Program at STAI Al Amin Dompu, in the application of oral da'wah, the obstacles faced by students of the Islamic Communication and Broadcasting Study Program in the application of oral dakwah, as well as knowing the efforts made by students. The Islamic Communication and Broadcasting Study Program in honing its readiness and ability in the application of oral dakwah. The application of the research used qualitative methods with data collection techniques through interviews and documentation. The objects of the research are students of the Islamic Communication and Broadcasting Study Program and supporting sources, namely the lecturers of the Islamic Communication and Broadcasting Study Program at the Sekolah Tinggi Agama Islam (STAI) in the Islamic Communication and Broadcasting Study Program. Dakwah Bil Lisan is a method of da'wah that uses one-way communication in general the congregation is passive. The preaching of oral bill includes lectures, speeches, sermons, religious discussions and so on. The abilities possessed by students of the Islamic Communication and Broadcasting Study Program are considered extraordinary because many of the sixth and eighth semester students are able to apply oral dakwah. Their abilities lead them to readiness to be brave enough to deliver oral dakwah, this is evidenced by the students who apply oral dakwah at religious events, competitions even during Friday sermons. Obstacles faced by students in implementing verbal speech are obstacles from within, namely nervousness which suddenly appears when they want to deliver oral speech messages besides that obstacles arise from mad'u, to overcome these obstacles students make efforts by sharpening His talents and interests include reading more Islamic books, participating in religious discussions and so on.